2019
DOI: 10.1002/jso.25437
|View full text |Cite
|
Sign up to set email alerts
|

Body surface area‐based vs concentration‐based perioperative intraperitoneal chemotherapy after optimal cytoreductive surgery in colorectal peritoneal surface malignancy treatment: COBOX trial

Abstract: Background and Objectives Cytoreductive surgery (CRS) and hyperthermic intraperitoneal perioperative chemotherapy (HIPEC) are the standard of care for patients diagnosed with colorectal peritoneal surface malignancy (PSM). Despite a clearly defined standardization of CRS, a large variety of HIPEC modalities are still used in clinical practice. Methods Body surface area (BSA)‐ and concentration‐based HIPEC protocols were clinically and pharmacologically evaluated in a randomized phase III clinical pilot trial. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 42 publications
3
19
0
Order By: Relevance
“…Although these findings cannot be easily extrapolated to in vivo tumour nodules in patients, it provides insight in the importance of the drug concentration in peritoneal fluid. As diffusion is the most dominant mechanism to penetrate in tissue for low-molecular-weight drugs, such as cisplatin and mitomycin C, higher drug concentration in peritoneal fluid results in higher drug concentration in tumour tissue [12]. Unfortunately, the optimal tissue concentration that is required to eliminate peritoneal metastases is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Although these findings cannot be easily extrapolated to in vivo tumour nodules in patients, it provides insight in the importance of the drug concentration in peritoneal fluid. As diffusion is the most dominant mechanism to penetrate in tissue for low-molecular-weight drugs, such as cisplatin and mitomycin C, higher drug concentration in peritoneal fluid results in higher drug concentration in tumour tissue [12]. Unfortunately, the optimal tissue concentration that is required to eliminate peritoneal metastases is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…This dosimetry of intraperitoneal oxaliplatin can be contrasted to the drug administration in the PRODIGE 7 protocol. The ultra-high dose of oxaliplatin (460 mg/m 2 ) was only about one-third absorbed in the short 30-minute intraperitoneal treatment [ 20 ]. The regional dose intensity was markedly reduced as compared to the study by Stewart et al The area under the curve for these two methods for oxaliplatin administration are different.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the COBOX trial showed recently that toxicity and efficacy of concentration based HIPEC protocols in patients suffering from colorectal PSM was higher. It was stated that the concentrationbased application is the most standardized way of chemotherapy delivering to the tumor tissue [16]. However, in both current dosing regimens, BSA is used as an estimate of PSA even if CRS has been performed before.…”
Section: Discussionmentioning
confidence: 99%